Literature Review: Pengaruh Digital Marketing dan Kualitas Produk terhadap Keputusan Pembelian - Farinda Hidayah Wati; Septiana Wati Era Lestari; Prayoga Alfian Nur Rohman; Tetra Hidayati (Teewan Journal Solutions, 2025)
This study aims to determine the effect of digital marketing and product quality on purchasing decisions using the Systematic Literature Review (SLR) method. This study was conducted by reviewing various relevant scientific articles in order to gain a comprehensive understanding of how digital marketing strategies and product quality can influence consumer decisions in making purchases. The results of the review show that digital marketing has a positive influence because it is able to attract consumers' attention through various digital platforms, while product quality is the main factor in forming consumer satisfaction and trust that drives purchasing decisions. This finding shows that both variables support each other in increasing consumer purchasing decisions.